Public capital and the demand for private inputs - Helmut Seitz (Zentrum für Europäische Wirtschaftsforschung (ZEW); ZBW – Leibniz Information Centre for Economics, 1992)
The paper investigates the impact the provision of public capital has on the demand for private capital and labour using a cost function with public capital included as a fixed unpaid factor of production. Special attention is paid to the examination of the influence tax vs. debt financing of public investment might have on the demand for private capital. The model is applied to a panel of 31 2-digit industries of the West German manufacturing industry. It is shown, that private and public capital are complements whereas a substitutive relation emerges for labour and public capital. Decomposing the adjustment of the demand for private labour and capital reveals a stabilizing but steadily decreasing impact of public capital on private inputs.
Keywords: E6; H3; H4; 330